P Pancasila Values and the Role of Religion in Family Education: Instilling Local Wisdom and Spirituality - Ul-haq, Fawwaz Dhiya; Natsir , Nanat Fatah; Fikri , Miftahul (Arbas: Journal of Educational Innovation, 2026)
This article discusses the integration of Pancasila values ​​and the role of religion in family education to instill local wisdom and spirituality. The study emphasizes the importance of these values ​​in shaping children's moral and spiritual development. It explores how Pancasila principles, such as belief in God, humanity, unity, democracy, and social justice, can be effectively integrated into daily family life. It also discusses the role of religious teachings in fostering moral values ​​such as compassion, honesty, and cooperation. This article highlights the importance of family education rooted in these values ​​in shaping a generation capable of facing global challenges while maintaining cultural identity and local wisdom.